Concluding remarks: the tropical legumes projects empowered communities in a wide variety of assets - Akpo, E.; Ojiewo, Christopher Ochieng; Omoigui, L.O.; Rubyogo, Jean-Claude; Varshney, Rajeev K. (Springer, 2020)
After 12 years of activity, the Tropical Legumes (TL) projects come to an end the year 2019. In addition to quantitative impact assessment, this publication brings to light various stakeholders’ own words about the kind of benefits they have made thanks to the TL projects. Research institutions, management and technical staff, extension services, NGOs, public and private seed companies, agro-dealers, farmer cooperatives, farmer groups, individual seed entrepreneurs, farmers, women farmers, processors, farm implement makers, and traders have all shared their unique impact stories for being part of TL III families.